High-Accuracy Localization Using IEEE 802.11 WiFi Legacy Preamble - Sean M. Ellison; Jeffrey A. Nanzer (IEEE Access, 2020)
We explore the use of synchronization bits from a standard 802.11 preamble for high-accuracy localization. The multi-tone short training field present in 802.11 standards that use a Legacy preamble is investigated in comparison to a common remote sensing waveform known as the stepped frequency waveform that shares similar waveform characteristics to the preamble. We present the 802.11 standard and the connection to the stepped frequency waveform, derive the theoretical lower bound on the short training field, present a comparison of simulated results, and present experimental wireless measurements demonstrating ranging accuracies on the order of 1.9 mm.